Konflik Poso : Sejarah dan Upaya Penyelesaiannya - Ilovia Ayaregita Widayat; Diana Mutiara Bahari; Azka Azzahra Salsabila; Nabila Rizky Sri Handayani; Hanna Khairunnisa Adjie (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
This paper analyzes the history of social conflicts that occurred in Poso district that began in 1992 and their efforts to resolve them. In general, this conflict is seen as a conflict in the name of the dominant religion, namely Islam and Christianity. This conflict is motivated by the displacement of social order in which the indigenous Poso people who mostly adhere to Christian beliefs feel marginalized by migrants, especially from Java, who are mostly Muslim. So this makes the social system move where the newcomers dominate in terms of politics, economics and social, giving rise to sentiment. In this study the authors used a qualitative method that uses sources of reading, literature, journals, books and online print media related to this research. The author uses two approaches namely the theory of constructivism and social conflict to answer the problems in this study. The results of this study stated that the main factor of social conflict that occurred in Poso was not due to religious dominance, but rather to the transfer of power both politically, economically and socially. In the solution, it met with obstacles and negotiations to find an amicable agreement that represented the interests of both parties.